Calcium-requiring step in the uptake of deoxyribonucleic acid molecules through the surface of competent pneumococci. - Seto, H (1976)
The conversion of surface-adsorbed deoxyribonucleic acid (DNA) molecules to a state in which they are inaccessible to exogenous deoxyribonuclease requires specifically calcium ions; magnesium ions cannot replace calcium ions. Virtually maximal levels of nuclease-resistant DNA binding and genetic transformation can be obtained in media free from magnesium and containing only calcium ions. It is suggested that the calcium-requiring process is the transport of DNA molecules across the plasma membrane. Magnesium ions stimulate both the loss of surface-adsorbed DNA to the medium and the extracellular degradation of DNA.